Case Report: Surgery to remove adrenocortical oncocytic carcinoma from an Asian male - Liu, Hongtao; Huang, Kai; Liu, Dan; Wang, Yehua (Frontiers in Surgery, 2023)
Adrenocortical oncocytic carcinoma is a rare type of adrenocortical tumor. Its clinical characteristics and biological behavior need to be further evaluated after the accumulation of cases. Here we report a case of adrenocortical oncocytic carcinoma in an Asian male with scoliosis. We performed an operation on this patient. Because the patient's scoliosis was limited during the operation and the tumor protruded into the chest, we decided to adopt open surgery in the supine position. During the operation, we found a tumor about 8 cm in diameter in the right adrenal region and successfully removed it. The patient recovered well after surgery, and there was no tumor recurrence after one year of follow-up. Pathological results confirmed the diagnosis of adrenocortical oncocytic carcinoma. Pathological features showed tumor cell invasion of adipose tissue, with atypical mitosis and abundant esinophilic cytoplasm. Immunohistochemistry showed that nucleus related antigen (Ki67) index was more than 15% and the positive pathological staining of Synaptophysin (Syn), Melanoma A (Melan A), Inhibin and calretinin. The incidence rate of adrenocortical oncocytic carcinoma is extremely rare. Abdominal Computed tomography (CT) scans and other imaging examination methods are not specific. For larger adrenal tumors, the diagnosis of this disease should be considered. For patients with adrenocortical oncocytic carcinoma who have not yet metastasized, we may achieve sound treatment effects and reduce recurrence by removing the tumor, retroperitoneal fat around the tumor and locoregional lymph nodes.